Relevance of Aβ42/40 Ratio for Detection of Alzheimer Disease Pathology in Clinical Routine: The PLMR Scale - Lehmann, Sylvain; Delaby, Constance; Boursier, Guilaine; Catteau, Cindy; Ginestet, Nelly; Tiers, Laurent; Maceski, Aleksandra; Navucet, Sophie; Paquet, Claire; Dumurgier, Julien; Vanmechelen, Eugeen; Vanderstichele, Hugo; et al. (Frontiers in Aging Neuroscience, 2018)
Background: Cerebrospinal fluid (CSF) biomarkers Aβ peptides and tau proteins improved the diagnosis of Alzheimer’s disease (AD) in research, and clinical settings. We previously described the PLM-scale (Paris-Lille-Montpellier study) which combines Aβ42, tau and phosphorylated ptau(181) biomarkers in an easy to use and clinically relevant way. The purpose of this work is to evaluate the interest of an optimized PLMR-scale (PLM ratio scale) that now includes the Aβ42/Aβ40 ratio to detect AD versus non-AD (NAD) participants in clinical routine of memory centers. Methods: Both scales were compared using 904 participants with cognitive impairments recruited from two independent cohorts (Mtp-1 and Mtp-2). The CSF Aβ42/Aβ40 ratio was measured systematically in Mtp-1, and only on biologically discordant cases in Mtp-2. Two different ELISA kit providers were also employed. The distribution of AD and NAD patients and the discrepancies of biomarkers profile were computed. Receiver Operating Characteristic curves were used to represent sensitivity and specificity for AD detection. The classification of patients with the Net Reclassification Index (NRI) was also evaluated. Results: 904 participants (342 AD, 562 NAD) were studied; 400 in Mtp-1 and 504 in Mtp-2. For AD patients, the mean CSF Aβ42 and CSF Aβ42/40 ratio was 553+/-216 and 0.069+/-0.022 in Mtp-1 and 702+/-335 and 0.045+/-0.020 in Mtp-2. The distribution of AD and NAD differed between the PLM and the PLMR scales (p<0.0001). The percentage AD well classified (class 3) increased with PLMR from 38% to 83% in Mpt-1 and from 33% to 53% in Mpt-2. A sharp reduction of the discordant profiles going from 34% to 16.3% and from 37.5% to 19.8%, for Mtp-1 and Mtp-2 respectively, was also observed. The AUC of the PLMR scale was 0.94 in Mtp-1 and 0.87 in Mtp-2. In both cohorts, the PLMR outperformed CSF Aβ42 or Aβ42/40 ratio. The diagnostic performance was improved with the PLMR with an NRI equal to 44.3% in Mtp-1 and 28.8% in Mtp-2. Conclusions: The integration of the Aβ42/Aβ40 ratio in the PLMR scale resulted in an easy-to-use tool which reduced the discrepancies in biologically doubtful cases and increased the confidence in the diagnosis in memory center.